Judicial cooperation in european private law - Cafaggi, Fabrizio; Law, Stephanie (Edward Elgar Publishing, 2017)
Notwithstanding increases in the scope for interaction between European and national courts, little research has been undertaken into the potential impact of institutional cooperation and dialogue in European private law making. This coherent collection of original chapters provides unique insights into these developments - with a particular focus on consumer law, and changes in national civil procedure via substantive law enforcement - from a broad range of stakeholders, including academics and judges from the EU and the US. Dialogue of both a vertical (between national and European courts) and horizontal (between national courts) nature is visible in the growing number of preliminary references to the CJEU in European private law. Combined with activism on the part of national courts and the growing importance of regulators, this dialogue brings about new forms of development of European private law. This book offers a case-based analysis of these processes, highlighting the need to focus on the instruments of dialogue and cooperation, and pressing beyond the prevailing focus on constitutional dialogue to reveal a new perspective on the private law sphere. Judicial Cooperation in European Private Law will appeal to scholars, students, practising lawyers and judges interested in the creation and development of European private law at both national and EU levels.